Relationship between Human Immunodeficiency Virus (HIV) Knowledge, HIV-Related Stigma, and HIV Testing among Young Black Adults in a Southeastern City - Okumu, Eunice; Jolly, David H.; Alston, Le’Marus; Eley, Natalie T.; Laws, Michelle; MacQueen, Kathleen M. (Frontiers in Public Health, 2017)
The southeast is identified as the epicenter of the nation’s human immunodeficiency virus (HIV) epidemic, accounting for nearly 44% of all persons living with a HIV diagnosis in the United States. HIV stigma and knowledge have been cited as some of the complex factors increasing risk of acquiring HIV within African-American communities. We sought to understand how HIV knowledge and HIV-related stigma impact HIV testing experience among young Black adults who completed a community-based participatory research survey in a Southeastern city. Survey measures were developed with active engagement among the research team and community members, with the goal of balancing community knowledge, interests and concerns with scientific considerations, and the realities of funding and the project timeline. A total of 508 of the 513 audio computer-assisted self-interview questionnaires completed were analyzed. Eighty-one percent of participants had ever tested and had an intention-to-test for HIV in the next 12 months. Overall, analyses revealed low HIV-related stigma and relatively moderate to high HIV knowledge among young Black adults in the Southeastern city. Logistic regression indicated that having ever tested for HIV was positively correlated with HIV knowledge [odds ratio (OR): 1.50; 95% confidence interval (CI): 1.23–1.84, p < 0.001], but inversely correlated with low HIV-related stigma (OR: 0.08; 95% CI: 0.01–0.76, p < 0.03). However, there were no significant relationships between HIV-related stigma, HIV knowledge, and intention-to test for HIV in the future. These findings suggest that reducing HIV-related stigma and increasing HIV knowledge are not sufficient in promoting HIV testing (i.e., intention-to-test) among young Black adults in this city, unless specific emphasis is placed on addressing internalized HIV-related stigma and misperceptions about HIV prevention and control.